Efektivitas Prenatal Yoga Terhadap Nyeri Punggung Pada Ibu Hamil Trimester Iii Di Klinik M Kabupaten Karawang Tahun 2024 - Trisiani, Desi; Susilawati , Lala (CV. Green Publisher Indonesia, 2025)
Back pain during pregnancy usually occurs due to stretching of the bones. This problem will continue in the form of recurrent injuries or appear continuously in worse conditions according to the course of the gestational age Efforts to overcome back pain complaints, namely yoga gymnastics, are part of non-pharmacological therapy that can reduce pain. Objective: To determine the effectiveness of Prenatal Yoga against back pain in pregnant women. Methods: This study is a type of experimental research with a pre-test post-test one group research design. The sample in this study is pregnant women, the sample size is 35 respondents. Sampling uses a total sampling technique, the instruments used are Prenatal Yoga SOP and questionnaires. Results: The results of this study are that before Prenatal Yoga the average back pain scale of pregnant women was 7.34, while after Prenatal Yoga the average back pain scale of pregnant women was 2.20. The statistical test using a parametric test, namely the Paired Sample T-Test, obtained a significance value of p-value = 0.000 (p-value < 0.05), meaning that there is a significant difference in the scale of back pain of pregnant women before and after Prenatal Yoga. Conclusion: There is an effect of prenatal yoga on back pain in pregnant women.